Solid Waste Management Ordinances: Compliance and Challenges - Abangan, Janine (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the level of compliance with solid waste management ordinances and the challenges encountered in their implementation in the Municipality of Trinidad, Bohol. Anchored on Policy Implementation Theory and Compliance Theory, the study analyzed how local solid waste management policies are translated into community practice and how stakeholder behavior affects compliance. A mixed-methods research design was used, combining survey questionnaires and Key Informant Interviews. The respondents included 272 survey participants composed of 6 barangay officials, 12 garbage collectors, and 254 household members, while 5 Local Solid Waste Management Board members served as key informants. Findings showed that compliance with solid waste management ordinances was generally high among barangay officials, garbage collectors, and household members, with overall means of 3.82, 3.80, and 3.59, respectively, all interpreted as fully complied. However, challenges remained, particularly among household members, who reported moderate difficulties related to plastic use, limited ordinance awareness, disposal habits, and accessibility concerns. Compliance levels did not significantly differ among respondent groups, but challenges encountered differed significantly, particularly between barangay officials and household members. The study concludes that Trinidad’s solid waste management ordinance implementation is generally effective but requires stronger household-focused education, improved access to waste management facilities, and institutionalized incentive and monitoring mechanisms. The study supports SDG 3, SDG 11, SDG 12, SDG 16, and SDG 17 by promoting healthier communities, sustainable barangays, responsible waste practices, stronger local governance, and stakeholder collaboration. Its sustainability impact lies in strengthening environmental protection, public health, community participation, and policy-based local governance.